Risk of Cardiovascular Events Among Patients Initiating Efavirenz-Containing Versus Efavirenz-Free Antiretroviral Regimens. (30th March 2016) - Rosenblatt, Lisa; Farr, Amanda M.; Johnston, Stephen S.; Nkhoma, Ella T.
Abstract : In this analysis of real-world data, there was no evidence of increased risk of cardiovascular events in patients initiating efavirenz-containing regimens compared to patients initiating efavirenz-free regimens, whether an intent-to-treat or as-treated follow-up period was used. Abstract: Background.  Efavirenz (EFV), an antiretroviral medication used to treat human immunodeficiency virus (HIV) infection, can increase lipid levels. Because hyperlipidemia is associated with increased risk for cardiovascular (CV) events, this study compared the risk of CV events in patients initiating EFV-containing vs EFV-free antiretroviral regimens. Methods.  Antiretroviral-naive HIV-positive (HIV+) patients ages 18–64 were selected from commercial and Medicaid insurance claims databases. Patients with ≥1 claim for antiretroviral medications between January 1, 2007 and December 31, 2013 were classified into 2 cohorts: EFV-containing or EFV-free regimens. Patients were required to have 6 months of continuous enrollment before initiation, with no evidence of a CV event during this time. Patients were observed from initiation until the occurrence of a CV event, disenrollment, or study end. Cardiovascular events were identified through diagnosis or procedure codes for myocardial infarction, stroke, percutaneous coronary intervention, or coronary artery bypass graft. We calculated unadjusted incidence rates (IRs) and fit propensity-score-weighted Cox proportional hazards models. Results.  There were 22 212 patients (11 978 EFV-containing and 10 234 EFV-free) identified in the commercial database and 7400 patients identified (2943 EFV-containing and 4457 EFV-free) in the Medicaid database. Cardiovascular events were rare (commercial IR = 396 per 100 000 person-years; Medicaid IR = 973 per 100 000 person-years). In propensity-score-weighted models, hazards of CV events were significantly lower for EFV-containing regimens in the commercial database (hazard ratio [HR] = 0.68; 95% confidence interval [CI], .49–.93) No significant difference was found in the Medicaid database (HR = 0.83; 95% CI, .58–1.19). Conclusions.  This analysis found no evidence of increased risk of CV events among HIV+ patients initiating EFV-containing regimens.